Repercusiones económicas y comerciales del tratado de paz entre Ecuador y Perú de 1998, entre los años 2007-2018. - Aguirre Valladares, Jorge Sebastián (2023)
After a definitive peace was achieved between Ecuador and Peru in 1998, both nations agreed on several economic, commercial, and social cooperation plans. The purpose of this study was to verify the fulfillment of these agreements and whether they have been fruitful for the society and economy of Ecuador between the years 2007 and 2018, for which a mixed research methodology was used, combining qualitative and quantitative methods, using a bibliographic design, collection techniques of documentary sources, financial data provided by the Central Bank of Ecuador, and indexed magazines and newspaper articles. The results obtained were a considerable increase in the exportation and importation of products between Ecuador and Peru, as well as the construction of energy, road, and academic infrastructure in the border regions of both nations. The resolution was that most of the commercial plans have been beneficial and successfully fulfilled, except for certain economic agreements regarding social development that still need to be fulfilled.